Expenditure patterns and social determinants of type II diabetes epidemic in the Coahuila-Texas border - José Luis MANZANARES-RIVERA (Universidad Autónoma del Estado de México, 2016)
Type II diabetes mortality growth during the last decade in Mexico is a subject of increasing concern with deep social implications, this is especially true at the eastern US-Mexico Border region. In this study, the goal is to analyze the relationship between consumption patterns and type II diabetes (T2D) mortality rates focusing in Coahuila, a Mexican state on the border with Texas. The base theoretical approach derives from the social determinants of health paradigm. To allow international comparability T2D definition complies with the International classification of disease ICD -2010 codes E100-E149 and the statistical analysis follows a two-stage process: exploratory data analysis (EDA) and an inferential stage using micro data from two main sources, the national household expenditure survey 2012 and the National Health information System SINAIS 2012. Results show that there is an important spatial effect and suggests that social determinants may provide supplementary elements to design local prevention policies towards improving public health.